IN 2020, INDONESIA IS FREE FROM CORRUPTION, AN IMPOSIBLE MISSION? - Mariyadi Mariyadi; Abdul Wahid (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Each element of the nations with a high commitment to the realization of the great interest of Indonesia certainly has an idealism that in 2020 the condition of this country will be better than now,  and it will also  be a strong, clean and  powerful country.  So far, Indonesia has still being stigmatized as a powerless country and even it is indicated as a failed country due to a large number of and various  diseases that undermine it.  There have been many diseases that have gnawed this country and that have gotten some places in making some  porosity to the construction of Indonesia since hundreds of years or since the republic of Indonesia was proclaimed.1 Meanwhile, one of the the greatest interests of this country that has been idealized is to reduce a disease  the scientists have thought to have a deep root in this country, corruption.  If this abuse of power may be maximally reduced, the fundamental interests such as prosperity and education of egalitarianism may be realized.  Is it possible to bring the great interest of the nation into reality?  Will this beloved Indonesia be free from corruption in 2020?  Is it an impossible mission supposed that we have an ideal that Indonesia will be free from any corruption in the next three years?